The Coastal Abrasion Mitigation Using Permeable Structure at The Sipora Island - Herdiana Mutmainah (Jurnal Teknik Sipil dan Perencanaan, 2025)
Abrasion is the beach erosion process due to destructive waves and currents, which are sometimes difficult to handle. The abrasion is caused by current, tidal, wind, and the earthquake and tsunami, 2010. Sipora Island is a world tourist destination for snorkeling, diving, and surfing. This research was conducted to mitigate abrasion at Sipora using a submerged permeable structure. The method is a quantitative analysis using permeable structure, WQC TOAA, current meter, and sediment trap. The field survey was conducted in August and October 2020 using purposive sampling at Kampung Dusun, Tua Pejat, The Sipora Island. The results show that the permeable structure can reduce the abrasion, current, and wave pressure and increase sedimentation at Kampung Dusun. The abrasion rate is 3.73 m/year or 268 m2/year, classified as very high (CVI). Sedimentation is created behind the permeable structure, whose rate is 9.389 cm3/day, sea current is 0.02-0.08 m/s (reduced till 50%), and wave pressure is 0.375 KN/m2 (decreased 62.5%). For seawater quality, the pH and turbidity are increased; TDS and salinity are relatively stable at some points, but the pH and temperature of the dissolved oxygen are decreased. The permeable structure can reduce abrasion and create sedimentation at Kampung Dusun, Sipora.